Class I KNOX is related to determinacy during the leaf development of the fern Mickelia scandens (Dryopteridaceae) - Cruz, Rafael; Melo-De-pinna, Gladys F. A.; Vasco, Alejandra; Prado, Jefferson [UNESP]; Ambrose, Barbara A. (MDPI, 2020)
Unlike seed plants, ferns leaves are considered to be structures with delayed determinacy, with a leaf apical meristem similar to the shoot apical meristems. To better understand the meristematic organization during leaf development and determinacy control, we analyzed the cell divisions and expression of Class I KNOX genes in Mickelia scandens, a fern that produces larger leaves with more pinnae in its climbing form than in its terrestrial form. We performed anatomical, in situ hybridization, and qRT-PCR experiments with histone H4 (cell division marker) and Class I KNOX genes. We found that Class I KNOX genes are expressed in shoot apical meristems, leaf apical meristems, and pinnae primordia. During early development, cell divisions occur in the most distal regions of the analyzed structures, including pinnae, and are not restricted to apical cells. Fern leaves and pinnae bear apical meristems that may partially act as indeterminate shoots, supporting the hypothesis of homology between shoots and leaves. Class I KNOX expression is correlated with indeterminacy in the apex and leaf of ferns, suggesting a conserved function for these genes in euphyllophytes with compound leaves.
Keywords: Apical meristems; Class I KNOX genes; Compound leaves; Determinacy; Dryopteridaceae; Ferns; Leaf development; Pinna development; Shoot development